PENGARUH DISIPLIN BELAJAR, CARA BELAJAR DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR - Inayati Sofiah; I Komang Winatha; Nurdin Nurdin (FKIP Unila, 2013)
This study aimed to determine the effect of the discipline of learning at home, how to learn, and the parents' attention on learning outcomes integrated IPS SMP Wiyatama eighth grade students. The method used is descriptive verification qith ex post facto approach and survey. The sampling technique used probability sampling with proportionate random sampling and using Taro Yaman formula. Hypothesis testing is using simple linear regression analysis and multiple. Based on the analysis of data, it is obtained : (1) There is an influence of the discipline of learning at home against IPS integrated learning outcomes (2) There is a way of studying the influence of IPS integrated learning outcomes (3) There is an influence of parental towards IPS integrated learning outcomes (4) There is an influence on the discipline of learning at home, how to learn and parents' attention on integrated IPS learning outcomes.Penelitian ini bertujuan mengetahui pengaruh disiplin belajar di rumah, cara belajar, dan perhatian orang tua terhadap hasil belajar IPS Terpadu siswa kelas VIII SMP Wiyatama. Metode penelitian yang digunakan adalah deskriptif verifikatif dengan pendekatan ex post facto dan survei. Teknik sampling adalah probability sampling dengan proportionate random sampling dan dihitung menggunakan rumus Taro Yaman. Pengujian hipotesis menggunakan analisis regresi linier sederhana dan multiple. Berdasarkan analisis data diperoleh: (1) Ada pengaruh disiplin belajar dirumah terhadap hasil belajar IPS terpadu (2) Ada pengaruh cara belajar terhadap hasil belajar IPS terpadu (3) Ada pengaruh perhatian orang tua terhadap hasil belajar IPS terpadu (4) Ada pengaruh terhadap disiplin belajar dirumah, cara belajar dan perhatian orang tua terhadap hasil belajar IPS terpadu.Kata kunci : cara belajar, disiplin belajar, hasil belajar, perhatian orang tua